Improving maternal and child health policymaking processes in Nigeria: an assessment of policymakers’ needs, barriers and facilitators of evidence-informed policymaking - Uneke, Chigozie J. (Health Res Policy Syst, 2017)
BACKGROUND: In Nigeria, interest in the evidence-to-policy process is gaining momentum among policymakers involved in maternal, newborn and child health (MNCH). However, numerous gaps exist among policymakers on use of research evidence in policymaking. The objective of this study was to assess the perception of MNCH policymakers regarding their needs and the barriers and facilitators to use of research evidence in policymaking in Nigeria. METHODS: The study design was a cross-sectional assessment of perceptions undertaken during a national MNCH stakeholders’ engagement event convened in Abuja, Nigeria. A questionnaire designed to assess participants’ perceptions was administered in person. Group consultations were also held, which centred on policymakers’ evidence-to-policy needs to enhance the use of evidence in policymaking. RESULTS: A total of 40 participants completed the questionnaire and participated in the group consultations. According to the respondents, the main barriers to evidence use in MNCH policymaking include inadequate capacity of organisations to conduct policy-relevant research; inadequate budgetary allocation for policy-relevant research; policymakers’ indifference to research evidence; poor dissemination of research evidence to policymakers; and lack of interaction fora between researchers and policymakers. The main facilitators of use of research evidence for policymaking in MNCH, as perceived by the respondents, include capacity building for policymakers on use of research evidence in policy formulation; appropriate dissemination of research findings to relevant stakeholders; involving policymakers in research design and execution; and allowing policymakers’ needs to drive research. The main ways identified to promote policymakers’ use of evidence for policymaking included improving policymakers’ skills in information and communication technology, data use, analysis, communication and advocacy. CONCLUSION: To improve the use of research evidence in policymaking in Nigeria, there is a need to establish mechanisms that will facilitate the movement from evidence to policy and address the needs identified by policymakers. It is also imperative to improve organisational initiatives that facilitate use of research evidence for policymaking. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12961-017-0217-5) contains supplementary material, which is available to authorized users.